2021
DOI: 10.1002/jcla.23858
|View full text |Cite
|
Sign up to set email alerts
|

The role of circRNA derived from RUNX2 in the serum of osteoarthritis and its clinical value

Abstract: Background Circular RNA (circRNA) has been shown to affect the pathological process of osteoarthritis (OA) and is expected to become a potential marker for disease diagnosis. This study aimed to investigate the association between circRNA derived from the gene of runt‐related transcription factor 2 (RUNX2) and OA risk. Methods The expression profile of RUNX2‐derived circRNAs in serum of OA patients was detected. Then, the cytological localization of screened differential circRNAs was studied. Luciferase (LUC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“… The previous study indicated that circ_0005526 was upregulated in serum of OA patients, and had clinical significance in OA [ 10 ]. Our evidences unraveled that circ_0005526 knockdown inhibited chondrocyte injury in IL-1β-induced OA model through mediating miR-142-5p/TCF4 axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… The previous study indicated that circ_0005526 was upregulated in serum of OA patients, and had clinical significance in OA [ 10 ]. Our evidences unraveled that circ_0005526 knockdown inhibited chondrocyte injury in IL-1β-induced OA model through mediating miR-142-5p/TCF4 axis.…”
Section: Discussionmentioning
confidence: 99%
“…elucidated that circ_0134111 aggravated inflammatory reaction and extracellular matrix degradation of chondrocytes in OA through downregulating suppressor of cytokine signaling 1 (SOCS1) by targeting miR-515-5p [ 9 ]. Circ_0005526 has been shown to function as miRNA sponges in OA [ 10 ], but the regulatory function of circ_0005526 remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, miR-665 was of particular interest among putative target miRNAs of circ_0037658. MiR-665 has been confirmed to play an important role in the circ_RUNX2-miRNA’s regulatory network in OA progression ( Wang C. et al, 2021 ). Furthermore, the dysregulation of miR-665 was closely associated with IL-1β-triggered cell damage in some relevant literature ( Wang et al, 2020 ; Ouyang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have reported the application of circRNAs as biomarkers for the diagnosis of OA [ 22 , 23 ], these studies only included HCs as true negative cases in ROC curve analysis. For instance, using increased serum expression levels of circ_RUNX2 as a biomarker, patients with OA were separated from controls [ 22 ]. In another study, the application of blood hsa_circ_0032131 in separating OA patients from the controls has also been investigated [ 23 ].…”
Section: Discussionmentioning
confidence: 99%